Factors Affect Employees Motivation: A Case Study of Ku Ka Sing Subdistrict Administrative Organization Amphoe Kaset Wisai, Roi-Et Province - Chuprasoe, Yutthasak (The Journal of Development Administration Research, 2019)
The objective is to study and compare factors that affect the motivation of the employees, success in work, the progress in the job position, respect for aspects of the work, job description and responsibility. The sample consisted of 68 staff members of the Ku Ka Sing Subdistrict Administrative Organization from 4,533 employees. The purposive sampling method was used to classify gender, age, marital status, education level. estimate salary the tool used to collect data is a questionnaire. Statistics used in Analysis of data such as percentage (average), mean (standard), standard deviation, hypothesis testing by using statistics, t-test and one-way ANOVA analysis. The research found that, factors Affect Employees Motivation the overall picture is at the highest level. descending order, success in work. In particular employees have developed their own strengths in their work. Followed by job description Especially in the determination of clear details of work and the appropriate amount of work as for the respect of being at the lowest level in particular, the work that employees do is a profession that has honor and recognition in society. Results of compare factors, it was found that gender, age and level of education to be differentiate. As well as to have effected to the factors affecting performance motivation of employees, in the part of the success of work, the progress in the position, self-respect, job description and responsibility another then, status of married, incomes per month to be differentiate, do not affect to performance motivation of employees, namely success in work, the progress in the job position, respect for aspects of the work done and responsibility